Cell-surface glycoprotein of oligodendrocyte progenitors involved in migration - Niehaus, Antje; Stegmüller, Judith; Diers-Fenger, Marianne; Trotter, Jacqueline (The journal of neuroscience, 1999)
Myelination by oligodendrocytes in the CNS involves the migration to and recognition and ensheathment of axons. These distinct developmental phases of myelination are assumed to involve the interplay of a precisely regulated set of cell adhesion molecules expressed by both neurons and glial cells. These molecules remain largely unelucidated. In this paper we have identified a large (330 kDa) glycoprotein expressed by murine oligodendrocyte progenitor cellsin vitro and in vivo that is downregulated as oligodendrocytes mature. Antigen-positive oligodendrocyte progenitor cells purified by panning develop into myelin-associated glycoprotein-positive oligodendrocytes and also adhere to cultured neurons. Polyclonal antibodies directed against the protein reduce the migration of oligodendrocyte progenitor cells. The observations suggest that the AN2 antigen may play a role in early stages of myelination.
Gesehen am 19.06.2017